2002
DOI: 10.1111/j.1349-7006.2002.tb01315.x
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Rats Carrying Human c‐Ha‐ras Proto‐oncogene Are Highly Susceptible to N‐Nitrosomethylbenzylamine Induction of Esophageal Tumorigenesis

Abstract: A transgenic rat line carrying three copies of the human c-Ha-ras proto-oncogene, including its own promoter region, has been established in our laboratory (Hras128 rats), and shown to be highly susceptible to induction of mammary and urinary bladder tumors. Mutation analysis of induced lesions indicated the majority to contain some but not all cells with transgene mutation. In the present study, the susceptibility of Hras128 rats to N-nitrosomethylbenzylamine (NMBA) induction of esophageal tumors was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(38 reference statements)
0
19
0
Order By: Relevance
“…N-nitrosomethylbenzylamine esophageal, 35) and DMBA skin carcinogenesis. 36) We recently showed that the transgenic (Tg) rats have a potential for use in medium-term bioassay models to test for the modifying effects of estrogenic environmental compounds on mammary tumor development.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…N-nitrosomethylbenzylamine esophageal, 35) and DMBA skin carcinogenesis. 36) We recently showed that the transgenic (Tg) rats have a potential for use in medium-term bioassay models to test for the modifying effects of estrogenic environmental compounds on mammary tumor development.…”
Section: )mentioning
confidence: 99%
“…Most of the tumor cells contained mutated transgene, but not endogenous Hras gene, indicating that activation of the transgene plays an important role in such rapid development of tumors. The animals have also been found to be susceptible to N-butyl-N-(4-hydroxybutyl)nitrosamine urinary bladder, 34) N-nitrosomethylbenzylamine esophageal, 35) and DMBA skin carcinogenesis. 36) We recently showed that the transgenic (Tg) rats have a potential for use in medium-term bioassay models to test for the modifying effects of estrogenic environmental compounds on mammary tumor development.…”
mentioning
confidence: 99%
“…7) In humans, Ki-ras mutations are preferentially found in colon, 8,9) pancreatic duct 10) and bile duct carcinomas, 11) and N-ras mutations are typically seen in myeloid leukemia. 12) We have generated a transgenic rat line, harboring copies of a human c-Ha-ras proto-oncogene (Hras128 rat), and have shown that these animals are highly susceptible to mammary, 13,14) bladder 15) and esophageal 16) carcinogens.…”
mentioning
confidence: 99%
“…These data suggest that mutational activation of the H-ras gene is important for progression of the premalignant lesions to papillomas. Additional evidence in support of this concept is the observation that transgenic rats carrying the human c-Ha-ras proto-oncogene are highly susceptible to the induction of esophageal tumors with NMBA (Asamoto et al, 2002). As has been found in human esophageal tumors, G:C→ A:T transition mutations have been observed in the p53 tumor suppressor gene in ∼30 % of rat esophageal papillomas (Lozano et al, 1994;.…”
Section: Rat Esophageal Tumor Modelmentioning
confidence: 74%